Comparing Criteria Standard of Some Physical and Functional Abilities Between Handball Players And Other Team sport Players - دروش رشيد أمين, عمار (Journal of Physical Education, 2019)
The Aim of the study revolves around specifying the most important physical and functional abilities as well as their tests. The study also aims at finding criteria standards of handball and other team sports (volleyball, basketball and soccer), in addition to the percentages of each variable understudy. Then these variables were compared with the criteria standards of each sport. The subjects were (62) international league players of the college of physical education/University of Baghdad. They were (17) handball player, (14) volleyball player, (12) basketball player and (19) soccer player of the academic year 2006 – 2007. The researcher achieved the above mentioned aims and a comparison was made between handball and the other team sports in criteria standards. Then the researcher finally recommended that coaches should pay attention to those sports and the players who represent the leagues of the college of physical education/ university of Baghdad.